Talent Management : A Research Overview - McDonnell, Anthony; Wiblen, Sharna (Oxford : Taylor & Francis Group, 2020)
Talent management is a central element of managerial discourse and organisational practice. A critical introduction for students, scholars and reflective practitioners, this shortform book guides readers through a relatively new and rapidly developing area of management research.
Cover -- Half Title -- Series Page -- Title Page -- Copyright Page -- Dedication Page -- Contents -- List of tables -- 1 Talent management: an introduction -- 2'Talent management' definitions, conceptualisations and frameworks -- 3 A kaleidoscope of'talent' definitions and conceptualisations -- 4 Talent identification: understanding how organisations could, should and do identify talent -- 5 Talent development: enhancing the value of talented individuals, talent pools or a combination of both -- 6 The impact of talent management: unpacking the evidence -- 7 Talent management and the future of work: a research agenda -- Index.
Description based on publisher supplied metadata and other sources.
Keywords: Personnel management-Research.